Experimental Investigation on the Properties of Compressed Soil Blocks Stabilized with Filter Cake, Marble Dust, and Cement - Yosef, Fanta (ASTU, 2022)
The Expansion Of The Construction Industry All Over The World Is In Needs Of Alternative Building Materials Since Conventional Materials Are In Short Supply And Also Cause Greatest Damage On Environment Due To Huge Consumption Of Scarce Resource And Energy As Well As Large Volume Emission Of Carbon Dioxide. Concerning These Issues, Scientists Searching For Sustainable And Eco-Friendly Building Materials For The Conservation Of The Environment And This Motivates The Application For The Development Of Compressed Stabilized Soil Blocks. The Study Presented In This Thesis Is Intended To Investigate Compressed Stabilized Soil Blocks Introduced As An Alternative Construction Material. The Study Of Soil Block Blended Effect Of Filter Cake And Marble Dust With Cement And The Lonely Effect Of Each Stabilizer On The Soil Of Adama Town Has A Lack Of Study For Soil Block Production. Hence, The Study Investigates Specific Properties Of Compressed Stabilized Soil Blocks To Make An Earnest Contribution Toward The Development Of This Building Material. Laboratory Tests Conducted On The Soil Of The Adama Area Used For The Study Provided Detailed Information On The Suitability Of Soil For Soil Block And The Result Proved That The Soil Is Suitable For Block Production. In The Study, Three Different Types Of Stabilizers Were Used: Cement, Marble Dust, And Filter Cake With 5%, 10%, And 15% Replacement Of Soil. Additionally, Marble Dust And Filter Cake Were Mixed with Cement With 2.5%, 5%, And 7.5% Of Each To Improve Their Efficiency. The Compressed Soil Block With Dimensions Of 290mm ??? ?140mm ?? 100mm Was Prepared And Cured For 28 Days. Finally, The Compressive Strength, Dry Density, And Water Absorption Of The Block Were Analyzed. Cement And Marble Dust Stabilized Blocks Had Better Compressive Strength And Density And Low Water Absorption Rate. While Filter Cake Stabilized Blocks Exhibited Poor Strength And Density And High Water Absorption But These Properties Were Improved When Filter Cake Was Blended With Cement. The Investigation Result Has Revealed That From The Blocks Produced At The Varying Total Stabilizer Contents From 5% Up To 15%, The Blocks Stabilized With Cement In Combination With Either Marble Dust Or Filter Cake Have High Compressive Strength And Low Water Absorption Rate Than The Block Produced Solely With Cement, Filter Cake And Marble Dust. The Economic Viability Of The Block Is Also Assessed. In General, The Study Examined The Interplay Between Constituent Materials Used (Cement, Filter Cake, Marble Dust, Soil, And Water) To Assess Their Effects.
Experimental Investigation On The Properties Of Compressed Soil Blocks Stabilized With Filter Cake, Marble Dust, And Cement
Keywords: sustainable development; stabilization; Filter cake; Marble Dust; compressed stabilized soil block; Sustainable Development; Stabilization; Filter Cake; Marble Dust; Compressed Stabilized Soil Block